2009
DOI: 10.1002/syn.20662
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent exposure of nicotine and smoke modulate ultrasubcellular organelle localization of dopamine D1 and D2 receptors in the rat caudate‐putamen

Abstract: The correlation of the subcellular localization of dopamine D(1) and D(2) receptors (DA D(1) R, DA D(2) R) with nicotine addiction has not been studied. We demonstrated the ultrasubcellular organelle localization of DA D(1) and D(2) Rs in the caudate-putamen (CPu) area of rat brain in vivo exposed to nicotine (3 mg/day; oral) and passive cigarette smoking (500 ml each; 3 times/day) for 1, 4, and 12 weeks, respectively. Our results revealed DA D(1) R localization in the presynaptic and postsynaptic dendrites, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
5
13
0
Order By: Relevance
“…5 Individual organ weights, foods, and water consumption were also not varied among the different study groups (data not shown), as mentioned previously.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…5 Individual organ weights, foods, and water consumption were also not varied among the different study groups (data not shown), as mentioned previously.…”
Section: Resultssupporting
confidence: 74%
“…In the CS group, two commercially available filtered cigarette (ITC, India) were passively inhaled for 1 hour in a tightly sealed whole-body inhalation chamber, and in the nicotine group, nicotine (Nic 3-9 mg/kg BW/day; dissolved in PBS) was administered orally, for 4 and 12 weeks as per our previous protocol. 5 The doses closely mimic the amount of nicotine intake as with the CS in human; 39 hence, the animal model used here may closely resemble the human situation. The control group was given PBS.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, Paulus et al (2005) demonstrated that activation in the insula, amongst other brain regions, predicted relapse in abstinent methamphetamine-dependent subjects. In addition, the putamen is supposed to play a role in addictive behavior through modulation of the mesolimbic dopaminergic system via D 1 and D 2 receptors (Ito et al, 2002;Naha et al, 2009). A limitation of the current study is that behavioral measures are not fully supportive for attentional bias to conditioned smoking cues in smokers.…”
Section: Discussionmentioning
confidence: 99%